MONOTONE CHAINS OF SETS IN OLYMPIAD PROBLEMS - Kurchenko, Olexandr; Syniavska, Olga (Physical and Mathematical Education, 2025)
Formulation of the problem. Problems in set theory and combinatorics are often found in middle and high school students at mathematics Olympiads. Such problems require students to apply not only theoretical knowledge but also logical reasoning and the use of non-standard methods. One of the effective methods for solving such problems is the use of monotonic chains of sets. With the help of monotonic chains, students can optimally solve problems of a particular type using the Dirichlet principle while applying fairly simple logical reasoning about the set and the structure of its subsets. The use of monotonic chains of sets in Olympiad problems is interesting from the point of view of preparing students for the Olympiad and from the point of view of forming students' mathematical competence. Such problems contribute to the development of logical and abstract thinking, the ability to analyze, generalize, build mathematical models, and apply well-known methods (for example, the Dirichlet principle). They stimulate students to use or seek out non-standard approaches.Materials and methods. The article used an analysis of scientific and educational literature, particularly manuals for preparing for mathematics Olympiads, as well as methods of set theory, combinatorics, and the Dirichlet principle.Results. The paper presents information from set theory about the set of all subsets of a specific set X, monotone chains of sets. It proves the statement about the minimal number of such chains for splitting the family of all subsets of a given set into monotone chains of sets. The problems are presented and solved using the described approach. They can be used in mathematical Olympiads and competitions at various levels.Conclusions. The method of monotone chains of sets is a convenient tool for solving Olympiad problems of a specific type. The presented results can be used to prepare students for mathematical Olympiads or competitions and for an in-depth study of the elements of set theory in a school mathematics course or extracurricular work.
Keywords: set; subset; binomial coefficient; monotone chains of sets; partition; Mathematical Olympiad